Factors associated with self-efficacy among patients with epilepsy in Turkey - OĞUZ, SIDIKA (ACADEMIC PRESS INC ELSEVIER SCIENCE, 2021)
Purpose: This study aimed to determine the self-efficacy levels of individuals with epilepsy and also compare individuals' self-efficacy with sociodemographic and epilepsy-related characteristics. Material and methods: The cross-sectional study was carried out with 200 individuals with epilepsy who were suitable for the inclusion criterias. Data were collected using patient information form which includes sociodemographic and clinical characteristics and Epilepsy Self-Efficacy Scale for evaluating epilepsy-related self-efficacy levels of patients. Results: The self-efficacy levels of the patients were moderate. Education, gender, occupational status, income, seizure frequency, regular use of medication, the number of drugs used, patient behavior following a drug-related problem, family support, the ability to obtain information about the illness, and hiding the illness from other people were significant factors determining scores on the epilepsy self-efficacy scale. Conclusion: This study confirms the findings of previous studies that were conducted to determine factors affecting self-efficacy. In order to increase self-efficacy, the findings show that there is a need for social support, education of epilepsy individuals, and information and awareness in society. (C) 2021 Elsevier Inc. All rights reserved.
Keywords: Epilepsy; Self-efficacy; Turkey